Biosensors: A Versatile Dual‐Emission Fluorescent Microhybrid Enabling Visual Detection of Glucose and Other Oxidases‐Based Biocatalytic Systems (Adv. Mater. Technol. 2/2016). Issue 2 (May 2016) - Lu, Xiaohui; Wang, Peipei; Wang, Yucong; Liu, Chenghui; Li, Zhengping
Abstract : Yucong Wang, Chenghui Liu, and co‐workers fabri‐cate a novel kind of dual‐emission micro‐hybrid (DEMBs) in article 1600024, by anchoring CdTe quantum dots on the surface of rhodamine‐embedded silica microbeads. The glucose‐responsive fluorescence color change of the DEMBs allows visual detection of glucose level in serum only by naked eye.